Taxa de câmbio e mudança estrutural: teoria e evidência - Fabricio Silveira (2011)
Exchange rate policy studies are nowadays in a prominent position inside macroeconomic discussions. However, despite the impressive progress of thetechniques, many important questions remain unanswered in the literature. This work fits in this context. It aims to study the active exchange rate policy effects on the economy structure, in order to justify the long-term effects ofthe real exchange rate on national product. To achieve this goal, it promotesthe adaptation of the traditional model of balance of payments constrainedgrowth and proposes a relationship between real exchange rate level,production structure and economic growth. New econometric evidence is provided so as to justify the assumptions. Finally we discuss some structural aspects of growth, something that has been mainly overlooked by the currentmacroeconomics, but believed to be crucial in determining the wellbeing levelof a nation.